Polyamidoamine hydrogel and a method for producing the same

KR1020260132264APending Publication Date: 2026-09-02SOGANG UNIV RES & BUSINESS DEV FOUND +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
KR1020250024924
Authority / Receiving Office
KR · KR
Patent Type
Applications
Current Assignee / Owner
Filing Date
2025-02-26
Publication Date
2026-09-02

Smart Images

  • Figure PAT00001_ABST
    Figure PAT00001_ABST
Patent Text Reader

Abstract

The present invention relates to a polyamidoamine hydrogel with a high amine group content and a method for manufacturing the same. By reacting an amine monomer and an acrylamide monomer without a stirring process, the primary amine content of the polyamidoamine hydrogel produced can be high, and accordingly, the polyamidoamine hydrogel can have excellent carbonate mineralization efficiency.
Need to check novelty before this filing date? Find Prior Art

Description

Technology Field

[0001] The present invention relates to a polyamidoamine hydrogel and a method for manufacturing the same. Background Technology

[0002] Due to recent industrialization, the concentration of carbon dioxide (CO2) in the atmosphere has been continuously increasing, intensifying the problems of global warming and ocean acidification. In particular, a significant amount of atmospheric carbon dioxide dissolves into seawater, forming carbonate (H2CO3) and bicarbonate ions (HCO3). - ), carbonate ions (CO3 2- It can exist in forms such as ), and during this process, ocean acidification occurs, in which the pH of the ocean decreases. This ocean acidification causes serious environmental problems such as coral bleaching, inhibition of shellfish growth, and disturbance of the marine ecosystem. Since this can have a negative impact not only on marine life but also on fisheries and the marine resource industry, research is currently underway on various measures to address ocean acidification.

[0003] As one of the above measures, a technology that effectively captures carbon dioxide in seawater and stably fixes it in the form of calcium carbonate (CaCO3) is attracting attention as an important solution. In nature, marine organisms such as shellfish and crustaceans also fix carbon dioxide by forming calcium carbonate through biological processes, but this biological mineralization process takes months to years, which limits its industrial application.

[0004] Accordingly, methods for fixing carbon dioxide using artificially synthesized polymers are attracting attention as a new alternative; however, these artificial synthetic polymer materials have the problem of causing microplastic issues in the marine environment due to their slow natural decomposition rate, and cross-linked polymers pose a significant environmental burden as decomposition is possible only through high-temperature treatment. Therefore, there is a need to develop new materials that can rapidly induce carbonate mineralization in seawater while simultaneously decomposing in an eco-friendly manner.

[0005] Meanwhile, polyamidoamine hydrogels formed from amine-based monomers and amide-based monomers have the advantage of being suitable as novel materials for fixing carbon dioxide in seawater because they are biodegradable and have excellent carbon dioxide fixation efficiency. However, there was a problem that it actually contradicted the original development objective of being eco-friendly, due to the use of toxic and harmful organic solvents such as toluene and surfactants in the process of manufacturing conventional polyamidoamine hydrogels, and the fact that the methanol purification process performed to recover the hydrogel particles could cause environmental pollution. In addition, there was a problem of poor economic feasibility because the cost required for the hydrogel manufacturing process increased due to the toxic organic solvents and the methanol purification process.

[0006] Therefore, there is a need to develop a novel method for manufacturing polyamidoamine hydrogels that are environmentally friendly and cost-effective, as well as polyamidoamine hydrogels that have performance equivalent to or better than conventional ones. The problem to be solved

[0007] The present invention relates to a method for manufacturing a polyamidoamine hydrogel without stirring during the polymerization process and a polyamidoamine hydrogel manufactured according to the same. The polyamidoamine hydrogel, which has a high content of primary amine groups, has the advantage of having excellent carbonate mineralization efficiency. means of solving the problem

[0008] To solve the above problems, the present invention provides a polyamidoamine hydrogel formed from an amine-based monomer and an acrylamide-based monomer, wherein the primary amine group content is 0.25 mmol / g or more.

[0009] The above amine-based monomer may contain two or more amine groups within the monomer.

[0010] The above acrylamide-based monomer may contain two or more acrylic groups within the monomer.

[0011] The above amine monomer may be one or more selected from the group consisting of ethylenediamine, 1,2-diaminopropane, 1,4-diaminobutane, hexamethylenediamine, diethylenetriamine, triethylenetetraamine, tris(2-aminoethyl)amine, diaminocyclohexane, and pentaethylenehexaamine.

[0012] The acrylamide-based monomer may be one or more selected from the group consisting of N,N'-methylenebisacrylamide, N,N'-(1,2-dihydroxyethylene)bisacrylamide, and N,N'-ethylenebisacrylamide.

[0013] The above polyamidoamine hydrogel may have a particle diameter of 1,000 μm or more and 5,000 μm or less.

[0014] The present invention provides a method for producing calcium carbonate by introducing the polyamidoamine hydrogel into an aqueous calcium ion solution to produce calcium carbonate.

[0015] The above calcium carbonate may have an aragonite-type crystal form.

[0016] It may be possible to add 1 kg or more of the polyamidoamine hydrogel based on 1 L of the above calcium ion aqueous solution.

[0017] The present invention provides a method for preparing a polyamidoamine hydrogel comprising the steps of: preparing a precursor mixture comprising an amine monomer, an acrylamide monomer, and an aqueous solvent (S10); and reacting the monomers in the precursor mixture to produce a polyamidoamine (S20), wherein the step (S20) is performed without stirring the precursor mixture, and the monomer content of the precursor mixture is 20 weight% or more.

[0018] The molar ratio of the above amine-based monomer and acrylamide-based monomer may be 1:0.5 or more and 1:3 or less.

[0019] The above (S10) step may involve a Michael addition reaction of the amine-based monomer and the acrylamide-based monomer.

[0020] The monomer content of the above precursor mixture may be 40% by weight or more and 80% by weight or less.

[0021] The above step (S20) may be performed at a temperature of 50°C or higher and 100°C or lower. Effects of the invention

[0022] The method for preparing a polyamidoamine hydrogel according to the present invention has the advantage of being environmentally friendly and economical as it uses an aqueous solvent for a short period of time without stirring. In addition, the polyamidoamine hydrogel prepared according to the present invention has the advantage of having a high primary amine group content and excellent carbonate mineralization efficiency. Brief explanation of the drawing

[0023] Figure 1 is a diagram illustrating the chemical structure of the polyamidoamine hydrogel of the present invention. FIG. 2 is a diagram showing the process of obtaining aragonite-type calcium carbonate from seawater using the polyamidoamine hydrogel of the present invention. Specifically, FIG. 2(a) is the polyamidoamine hydrogel of Preparation Example 1 of the present invention, and (b) is an image of the polyamidoamine hydrogel immersed in artificial seawater. (c) is an image of the polyamidoamine hydrogel immersed in distilled water after filtering and washing, (d) is an image of the polyamidoamine hydrogel hydrolyzed by distilled water and immersed in aragonite-type calcium carbonate, and (e) is an image of the finally obtained aragonite-type calcium carbonate. Figure 3 is a scanning electron microscope image of the surface of the polyamidoamine hydrogel of Preparation Example 1. Figure 4 is a graph showing the results of analyzing the polyamidoamine hydrogel (Pristine PAMAM) of Preparation Example 1 and the aragonite-type calcium carbonate (Isolated CaCO3) obtained according to Example 5' using a Fourier transform-infrared spectrometer. Figure 5 is a scanning electron microscope image of the surface of aragonite-type calcium carbonate precipitated according to Example 5'. Figure 6 is a graph showing the results of X-ray diffraction analysis of aragonite-type calcium carbonate (detached CaCO3) obtained according to Example 5'. Figure 7 is a graph showing the thermogravimetric analysis results of aragonite-type calcium carbonate (isolated CaCO3) obtained according to Example 5'. FIG. 8 is a graph showing the thermogravimetric analysis results of the polyamidoamine hydrogel (Pristine PAMAM) of Preparation Example 1 and the polyamidoamine hydrogel-calcium carbonate composite (8 day) immersed in artificial seawater for 8 days according to Example 5'. Figure 9 is a graph showing the carbonation mineralization efficiency of Examples 1' to 5', and compares the carbonation mineralization efficiency according to the artificial seawater immersion time. Figure 10 is a graph showing the absorbance of the polyamidoamine hydrogels of Preparation Example 1, Comparative Preparation Examples 1 and 2 analyzed by the infrared visible light method. Figure 11 is a concentration-absorbance graph showing the absorbance of the polyamidoamine hydrogels of Preparation Example 1, Comparative Preparation Examples 1 and 2 and the absorbance detected from the ethylenediamine standard concentration solution as a function of concentration. Specific details for implementing the invention

[0024] Hereinafter, each component of the present invention is described in more detail so that a person skilled in the art to which the present invention pertains can easily implement it; however, this is merely an example, and the scope of the rights of the present invention is not limited by the following.

[0025] In this specification, the term “comprising” is used when listing materials, compositions, devices, and methods useful to the present invention, and is not limited to the examples listed.

[0026] In this specification, the terms “about” and “substantially” are used to mean a range of numerical or degree or an approximation thereof, taking into account inherent manufacturing and material tolerances, and are used to prevent an infringer from unfairly exploiting the disclosure in which precise or absolute figures provided to aid in understanding the invention are mentioned.

[0027] In this specification, when a component is described as being "on" one component, this means that, unless specifically stated otherwise, other components may be placed in between, without excluding the placement of other components.

[0028] In this specification, "amine monomer" refers to a monomer comprising an intramolecular amine functional group. The amine monomer is NH a -C x H yIt can be expressed by a chemical formula such as D0, wherein x and y are each integers from 1 to 20, a is 1 or 2, and D0 is a hydrocarbon group having 1 to 20 carbon atoms substituted or unsubstituted with hydrogen, oxygen, or nitrogen. Additionally, the amine monomer has the chemical formula structure described above (NH a -C x H y It is not limited to D0), and additional functional groups may be further bonded to the amine group and hydrocarbon group.

[0029] In this specification, "acrylamide monomer" means a monomer comprising an acrylamide structure within the molecule. For example, the acrylamide monomer may be represented by a chemical formula such as CH2=CHC(O)ND1D2, where D1 and D2 are each independently hydrogen, nitrogen, oxygen, or a substituted or unsubstituted hydrocarbon group having 1 to 20 carbon atoms. Furthermore, the acrylamide monomer is not limited to the chemical formula structure described above (CH2=CHC(O)ND1D2) and may have additional functional groups attached to the carbon double bond.

[0031] The present invention will be described in more detail below.

[0033] The present invention provides a polyamidoamine hydrogel.

[0034] According to one embodiment of the present invention, the polyamidoamine hydrogel is a polyamidoamine hydrogel formed from an amine-based monomer and an acrylamide-based monomer, characterized by having a primary amine group content of 0.25 mmol / g or more. The polyamidoamine hydrogel is a hydrogel in which a cross-linked network structure is formed by the Michael addition reaction between the amine group of the amine-based monomer and the acrylate group of the acrylamide-based monomer. The hydrogel induces the coordination bonding of calcium ions by the hydrolysis of the acrylamide group in an aqueous solution containing calcium, such as seawater, while simultaneously raising the pH of the aqueous solution to the level of 8 due to the local pH-raising effect caused by the amine group. Accordingly, it can effectively absorb carbonate ions to effectively form aragonite-type calcium carbonate. In the manner described above, the polyamidoamine hydrogel of the present invention has the advantage of being able to effectively fix carbon dioxide present in seawater by forming calcium carbonate.

[0035] In addition, the polyamidoamine hydrogel is characterized by having a primary amine group content of 0.25 mmol / g or more. Specifically, the primary amine group content of the polyamidoamine hydrogel may be 0.25 mmol / g or more, 0.275 mmol / g or more, 0.30 mmol / g or more, 0.325 mmol / g or more, or 0.35 mmol / g or more, and may also be 1 mmol / g or less, 0.8 mmol / g or less, 0.6 mmol / g or less, or 0.4 mmol / g or less. When the primary amine group content of the polyamidoamine hydrogel satisfies the above ranges, the amine groups rapidly capture carbon dioxide in seawater to form bicarbonate (HCO3). - ) can be formed, and accordingly, the above bicarbonate and calcium ions (Ca 2+This reaction can improve the rate at which calcium carbonate precipitates. In addition, it can prevent the excessive dissociation and loss of carbonate ions caused by the local pH increase due to the amine group during the carbon dioxide capture process, thereby allowing for the formation of a larger amount of calcium carbonate.

[0037] According to one embodiment of the present invention, the amine-based monomer may contain two or more amine groups within the monomer. Since the amine-based monomer contains two or more amine groups, it can form more bonds with more acrylamide-based monomers per amine-based monomer through a Michael addition reaction, thereby forming a polyamidoamine hydrogel with a high crosslinking density, which can result in excellent durability of the hydrogel. Furthermore, regarding the method for manufacturing a polyamidoamine hydrogel to be described later, the amine-based monomer containing two or more amine groups has a high reaction rate with the acrylamide-based monomer, so the productivity of the polyamidoamine hydrogel itself can also be excellent. Moreover, as described above, the high content of amine groups can lead to an excellent rate of precipitating calcium carbonate from seawater, and as a result of the localized increase in pH due to the amine groups, the pH buffering effect in seawater is excellent, and aragonite-type calcium carbonate can be effectively produced.

[0039] According to one embodiment of the present invention, the acrylamide-based monomer may contain two or more acrylic groups within the monomer. Since the acrylamide-based monomer contains two or more acrylic groups, it can form more bonds with more amine-based monomers per acrylamide-based monomer through a Michael addition reaction, thereby forming a polyamidoamine hydrogel with a high crosslinking density, which can result in excellent durability of the hydrogel. Furthermore, regarding the method for manufacturing a polyamidoamine hydrogel to be described later, the acrylamide-based monomer containing two or more acrylic groups has a high reaction rate with the amine-based monomer, so the productivity of the polyamidoamine hydrogel itself can also be excellent. Moreover, since a polyamidoamine hydrogel with a high acrylic group content can be modified through the acrylic groups, it has the advantage of being applicable as a functional hydrogel.

[0041] According to one embodiment of the present invention, the amine monomer may be one or more selected from the group consisting of ethylenediamine, 1,2-diaminopropane, 1,4-diaminobutane, hexamethylenediamine, diethylenetriamine, triethylenetetraamine, tris(2-aminoethyl)amine, diaminocyclohexane, and pentaethylenehexaamine. Specifically, the amine monomer may contain two or more primary amine groups, such as ethylenediamine and hexamethylenediamine, and accordingly, a polyamidoamine hydrogel with a high amine group content may have a high carbonate mineralization efficiency.

[0043] According to one embodiment of the present invention, the acrylamide-based monomer may be one or more selected from the group consisting of N,N'-methylenebisacrylamide, N,N'-(1,2-dihydroxyethylene)bisacrylamide, and N,N'-ethylenebisacrylamide. Specifically, the acrylamide-based monomer may contain two or more acrylic groups, such as N,N'-methylenebisacrylamide, and accordingly, the polyamidoamine hydrogel with high crosslinking density has excellent durability and can maintain excellent carbonate mineralization efficiency even when used multiple times.

[0045] According to one embodiment of the present invention, the polyamidoamine hydrogel may have a particle diameter of 1,000 μm or more and 5,000 μm or less. Specifically, the polyamidoamine hydrogel may have a particle diameter of 1,000 μm or more, 1,200 μm or more, 1,400 μm or more, 1,600 μm or more, or 2,000 μm or more, and may also have a particle diameter of 5,000 μm or less, 4,500 μm or less, 4,000 μm or less, 3,500 μm or less, 3,000 μm or less, 2,500 μm or less, or 2,000 μm or less. When the particle diameter of the polyamidoamine hydrogel satisfies the above range, the specific surface area of ​​the hydrogel particles is high, so the carbonate mineralization rate is fast, and at the same time, the hydrolysis of the hydrogel itself occurs slowly, allowing carbonate mineralization to take place over a longer period of time. Therefore, the polyamidoamine hydrogel satisfying the above particle diameter range can have excellent carbonate mineralization efficiency.

[0047] The present invention provides a method for producing calcium carbonate using a polyamidoamine hydrogel.

[0048] The above method for producing calcium carbonate may be a method for producing calcium carbonate from an aqueous solution of calcium ions, such as seawater, using the polyamidoamine hydrogel described above, and below, parts that overlap with the content regarding the polyamidoamine hydrogel will be omitted.

[0049] According to one embodiment of the present invention, the method for producing calcium carbonate may involve introducing the polyamidoamine hydrogel into an aqueous calcium ion solution to produce calcium carbonate. Specifically, the method for producing calcium carbonate may comprise the steps of: introducing the polyamidoamine hydrogel into an aqueous calcium ion solution, such as artificial seawater or actual seawater, under conditions of room temperature and atmospheric pressure; precipitating calcium carbonate on the surface of the polyamidoamine hydrogel to form a polyamidoamine hydrogel-calcium carbonate complex; and separating and obtaining high-purity calcium carbonate from the polyamidoamine hydrogel-calcium carbonate complex. The aqueous calcium ion solution contains calcium ions (Ca 2+ The concentration of ) is 400 mg / L or higher, carbonate (CO3 - It may be a calcium aqueous solution with a concentration of 200 mg / L or more, such as artificial seawater or real seawater.

[0051] According to one embodiment of the present invention, the calcium carbonate may have an aragonite-type crystal form. The method for manufacturing the calcium carbonate may involve controlling the pH of an aqueous calcium ion solution to 8 or higher using a polyamidoamine hydrogel, thereby forming aragonite-type calcium carbonate. As can be seen from the scanning electron microscope image in FIG. 5, the X-ray diffraction analysis result in FIG. 6, and the thermogravimetric analysis result in FIG. 7, the method for manufacturing the calcium carbonate may involve forming calcium carbonate having an aragonite-type crystal form. The aragonite-type calcium carbonate has the advantage of high strength, making it applicable in various fields, such as being used as a coating agent for plastics, rubber, paper, etc., or as a building material.

[0053] According to one embodiment of the present invention, the method for producing calcium carbonate may involve adding 1 kg or more of the polyamidoamine hydrogel per 1 L of the calcium ion aqueous solution. Specifically, the amount of the polyamidoamine hydrogel added per 1 L of the calcium ion aqueous solution may be 1 kg or more, 1.5 kg or more, or 2 kg or more, and may also be 5 kg or less, 4 kg or less, 3 kg or less, or 2 kg or less. When the amount of the polyamidoamine hydrogel added satisfies the above range, not only is it easy to adjust the pH of the calcium ion aqueous solution without a separate pH adjuster, but there is also an advantage of being economical as a sufficient amount of calcium carbonate can be obtained relative to the amount of hydrogel added.

[0055] The present invention provides a method for manufacturing a polyamidoamine hydrogel.

[0056] The method for manufacturing the above-described polyamidoamine hydrogel may be the method for manufacturing the polyamidoamine hydrogel described above, and below, parts that overlap with the content regarding the above-described polyamidoamine hydrogel will be omitted.

[0057] According to one embodiment of the present invention, a method for preparing a polyamidoamine hydrogel comprises the step (S10) of preparing a precursor mixture comprising an amine-based monomer, an acrylamide-based monomer, and an aqueous solvent, and the step (S20) of reacting the monomer in the precursor mixture to prepare a polyamidoamine, wherein the step (S20) is performed without stirring the precursor mixture, and the monomer content of the precursor mixture is 20 weight% or more.

[0058] Specifically, the method for manufacturing the polyamidoamine hydrogel is characterized by having a monomer concentration of 20% by weight or higher in the precursor aqueous solution. The monomer content refers to the total content of the amine-based monomer and the acrylamide-based monomer. Since the monomer concentration in the precursor aqueous solution is 20% by weight or higher in step (S20), the crosslinking reaction for hydrogel formation can occur across the entire range of the precursor aqueous solution even at temperatures of 100°C or lower, using only the monomer without a separate crosslinking agent. Furthermore, when the monomer content of the precursor mixture satisfies the above range, the reaction rate of the monomer is accelerated due to the high monomer concentration, allowing the hydrogel to be formed in a short period of time.

[0059] In addition, the above manufacturing method is characterized by the fact that the step (S20), in which the polymerization reaction of the monomer is performed according to the Michael addition reaction of the monomer, is performed without stirring of the precursor mixture, so the speed of Brownian motion for crosslinking is slow. Accordingly, non-uniformity of the polymerization reaction within the precursor mixture may occur, and some amine groups of the amine-based monomer do not participate in the Michael addition reaction, so as a result, a polyamidoamine hydrogel with a high content of primary amine groups within the aforementioned range may be formed. Furthermore, unlike conventional hydrogel manufacturing methods, the method for manufacturing the polyamidoamine hydrogel has the advantage of being environmentally friendly in that it does not use any toxic organic solvents such as toluene.

[0061] According to one embodiment of the present invention, the molar ratio of the amine monomer and the acrylamide monomer may be 1:0.5 or higher and 1:3 or lower. Specifically, the molar ratio of the amine monomer and the acrylamide monomer may be 1:0.5 or higher, 1:0.75 or higher, or 1:1 or higher, and may also be 1:3 or lower, 1:2 or lower, or 1:1 or lower. When a precursor mixture is prepared by adjusting the molar ratio of the amine monomer and the acrylamide monomer to the above range in step (S10), the content of the amine monomer and the acrylamide monomer in the precursor mixture is balanced, so a polyamidoamine hydrogel with high crosslinking density and excellent durability can be produced. In addition, there is an advantage that a polyamidoamine hydrogel with excellent carbonate mineralization efficiency can be produced because the content of the amine monomer is sufficient.

[0063] According to one embodiment of the present invention, step (S10) may involve a Michael addition reaction of the amine monomer and the acrylamide monomer. The amine monomer and the acrylamide monomer may not only be involved in step (S20) as described above, but may also be involved in a precursor mixture of the amine monomer and the acrylamide monomer to primarily form a low molecular weight polyamidoamine hydrogel, and further Michael addition reaction may be performed in step (S20), which is a subsequent full-scale polymerization step, to produce a polyamidoamine hydrogel having a stable cross-linked structure.

[0065] According to one embodiment of the present invention, the monomer content of the precursor mixture may be 40 wt% or more and 80 wt% or less. Specifically, the monomer content of the precursor mixture may be 40 wt% or more, 45 wt% or more, 50 wt% or more, or 55 wt% or more, and may also be 80 wt% or less, 70 wt% or less, or 60 wt% or less. When the monomer content of the precursor mixture satisfies the above range, the hydrogel formation reaction of step (S20) can be carried out within a short time due to the high monomer content. Furthermore, when the monomer content of the precursor mixture satisfies the above range, the monomers within the precursor mixture exist homogeneously, making it possible to manufacture a hydrogel with excellent durability and high swelling degree. Additionally, there is an advantage that the high amine group content in the hydrogel can result in excellent carbonate mineralization efficiency, while the high porosity facilitates ion diffusion.

[0067] According to one embodiment of the present invention, the step (S20) may be performed at a temperature of 50°C or higher and 100°C or lower. Specifically, the temperature of the step (S20) may be 50°C or higher, 60°C or higher, or 70°C or higher, and may also be 100°C or lower, 90°C or lower, or 80°C or lower. When the reaction temperature of the step (S20) satisfies the above range, the reaction rate of the monomer is fast, so the hydrogel can be manufactured in a short period of time. In addition, since the reaction temperature is not excessively high, unnecessary side reactions or decomposition of products or monomers can be prevented.

[0069] Hereinafter, the present invention will be described in detail with reference to examples to specifically explain the invention. However, the embodiments according to the present invention may be modified in various different forms, and the scope of the present invention is not to be interpreted as being limited to the embodiments described below. The embodiments of this specification are provided to more completely explain the present invention to those with average knowledge in the art.

[0071] Examples and Comparative Examples

[0072] Preparation of polyamidoamine hydrogel

[0073] <Preparation Example 1>

[0074] After adding 1.949 g (32.43 mmol) of ethylenediamine to 12.5 mL of water, the aqueous solution containing the ethylenediamine (EDA) was placed into a 100 mL beaker containing 5 g (32.43 mmol) of N,N'-methylenebisacrylamide (MBA) (monomer content approximately 56 wt%). Subsequently, a precursor mixture was prepared by heating in an 80°C water bath for 3 minutes.

[0075] The above precursor mixture was placed in a mold (size per grid: width × length × height = 0.5 cm × 0.5 cm × 0.3 cm) and reacted in an 80°C oven for 30 minutes without stirring. Afterward, a cross-linked polyamidoamine hydrogel was separated from the mold and obtained.

[0076] <Preparation Example 2>

[0077] In the above Preparation Example 1, a polyamidoamine hydrogel was obtained in the same manner as in Preparation Example 1, except that the reaction time in the oven at a temperature of 80°C was changed to 1 hour.

[0078] <Preparation Example 3>

[0079] In the above Preparation Example 1, a polyamidoamine hydrogel was obtained in the same manner as in Preparation Example 1, except that the reaction time in the 80°C oven was changed to 8 hours.

[0080] <Preparation Example 4>

[0081] In the above Preparation Example 1, a polyamidoamine hydrogel was obtained in the same manner as in Preparation Example 1, except that the reaction time in the oven at an 80°C temperature was changed to 10 hours.

[0082] <Preparation Example 5>

[0083] In the above Preparation Example 1, a polyamidoamine hydrogel was obtained in the same manner as in Preparation Example 1, except that the reaction time in the 80°C oven was changed to 24 hours.

[0084] <Preparation Example 6>

[0085] In the above Preparation Example 1, a polyamidoamine hydrogel was obtained in the same manner as in Preparation Example 1, except that hexamethylenediamine (HMDA) was used instead of ethylenediamine.

[0086] <Comparative Manufacturing Example 1>

[0087] In the above Preparation Example 1, a polyamidoamine hydrogel was obtained in the same manner as in Preparation Example 1, except that the precursor mixture was reacted by continuously stirring in an 80°C oven for 30 minutes.

[0088] <Comparative Preparation Example 2>

[0089] After adding 1.949 g (32.43 mmol) of ethylenediamine to 12.5 mL of water, the aqueous solution containing the ethylenediamine (EDA) was placed into a 100 mL beaker containing 5 g (32.43 mmol) of N,N'-methylenebisacrylamide (MBA). Subsequently, a precursor mixture was prepared by heating in an 80°C water bath for 3 minutes. To the precursor mixture, 87.5 mL of toluene and 0.0347 g of the surfactant sorbitan monostearate (Span 60) were added, and a reverse-phase suspension polymerization reaction was performed by stirring in an 80°C water bath for 30 minutes. After the reaction, the remaining toluene and surfactant were removed from the product to obtain a polyamidoamine hydrogel.

[0091] Experimental Example

[0092] Experimental Example 1. Evaluation of Carbon Dioxide Mineralization Efficiency

[0093] The carbon dioxide mineralization efficiency was evaluated using the polyamidoamine hydrogels of the above Preparation Example and Comparative Preparation Example. Specifically, 400 mg of the polyamidoamine hydrogels of the Preparation Example and Comparative Preparation Example was Ca 2+ The polyamidoamine hydrogel-calcium carbonate composite with calcium carbonate precipitated on the surface was immersed in 400 mL of artificial seawater with an ion concentration of 440 mg / L for 4 days. The polyamidoamine hydrogel-calcium carbonate composite was filtered and washed with distilled water at least 3 times, then dried in a vacuum oven for 3 days to obtain the polyamidoamine hydrogel-calcium carbonate composite. Next, the polyamidoamine hydrogel-calcium carbonate composite was ground with a mixer to prepare a powdered sample. In the same way, the polyamidoamine hydrogel before immersion in artificial seawater was prepared as a powdered sample.

[0094] The prepared powdered samples were analyzed using a thermogravimetric analyzer to calculate the amount of mineralized calcium carbonate (CaCO3) after loading. The amount of mineralized calcium carbonate was set based on 550°C, prior to the thermal decomposition of calcium carbonate, and the carbonate mineralization efficiency was evaluated using Equation 1 below. The mass fraction (%) at 550°C obtained by thermogravimetric analysis of the polyamidoamine hydrogel before loading into artificial seawater and the mass fraction (%) at 550°C of the polyamidoamine hydrogel-calcium carbonate composite obtained after loading were W, respectively. p W M It was expressed as, and the weight of the polyamidoamine hydrogel before mineralization was M p , the weight of the polyamidoamine hydrogel after mineralization is M M It was indicated as.

[0095] In Equation 1 below, (W M - W p ) is the mass fraction of calcium carbonate in the polyamidoamine hydrogel-calcium carbonate complex, and the mass M after mineralization M The mass of calcium carbonate can be calculated by multiplying by the calculated mass of calcium carbonate. The carbonate mineralization efficiency is calculated as a percentage by dividing the calculated mass of calcium carbonate by the mass of the polyamidoamine hydrogel before mineralization.

[0097] [Equation 1]

[0098] Carbonate mineralization efficiency (%) = (W M - W p ) × M M / M P × 100 (%)

[0100] division Hydrogel used Polymerization reaction time (time) Whether to stir during polymerization Carbonate mineralization efficiency (%) Example 1 Preparation Example 1 0.5 × 24.38 Example 2 Preparation Example 2 1 × 26.94 Example 3 Preparation Example 3 8 × 27.93 Example 4 Preparation Example 4 10 × 26.66 Example 5 Preparation Example 5 24 × 27.92 Example 6 Preparation Example 6 0.5 × 41.82 Comparative Example 1 Comparative Manufacturing Example 1 0.5 ○ 17.16 Comparative Example 2 Comparative Manufacturing Example 2 0.5 ○ 17.40

[0102] In addition, the content of primary amine functional groups in the polyamidoamine hydrogels was measured and compared for Example 1 and Comparative Examples 1 and 2. Specifically, 100 mg of the polyamidoamine hydrogel by dry weight, 2 mL of a 1 wt% aqueous solution of Ninhydrin ethanol, 1 mL of distilled water, and 1 mL of a sodium acetic acid buffer solution with a pH of 5.2 were placed in a vial and reacted in an oven at 100°C for 10 minutes. After the reaction, the solution was measured three times for each sample in the range from 800 nm to 400 nm using an Agilent Cary 100 UV-vis spectrophotometer, and the average value of the absorbance at 570 nm was calculated. In order to quantify the content of primary amine functional groups from the absorbance described above, the absorbance was measured after reacting in the same manner with 1 mL of each ethylenediamine aqueous solution at reference concentrations of 2.5 mM, 3.75 mM, 5.00 mM, 6.25 mM, and 7.50 mM, and the calibration curve equation of Equation 2 below was calculated. After calculating the concentrations by substituting the measured absorbances of Example 1, Comparative Examples 1 and 2 into the calibration curve equation, the primary amine functional group content (mmol / g) for each case was calculated by substituting them into Equation 3 below.

[0104] [Equation 2]

[0105] Calibration curve equation: Concentration(mM) = (Absorbance + 0.08343) / 0.10469

[0107] [Equation 3]

[0108] Primary amine functional group content (mmol / g) = Concentration (mmol / L) × 0.004 (L) / 0.1 (g)

[0110] division Hydrogel used Primary amine functional group content (mmol / g) Example 1 Preparation Example 1 0.385 Comparative Example 1 Comparative Manufacturing Example 1 0.230 Comparative Example 2 Comparative Manufacturing Example 2 0.145

[0112] As shown in Table 1 above, it can be confirmed that the polyamidoamine hydrogel prepared by reacting monomers without stirring according to the method of the present invention has high carbonate mineralization efficiency despite the short reaction time of approximately 30 minutes. Furthermore, excellent carbonate mineralization efficiency was observed across a wide reaction time range of 30 minutes to 24 hours, and in particular, the polyamidoamine hydrogel of Preparation Example 6, prepared using hexamethyldiamine as the amine monomer, was confirmed to have significantly high carbonate mineralization efficiency. On the other hand, as shown in Table 2 above, the polyamidoamine hydrogel of Comparative Preparation Example 1, prepared by reacting a precursor mixture with stirring, as well as the polyamidoamine hydrogel of Comparative Preparation Example 2, prepared through reverse-phase suspension polymerization accompanied by stirring, had a lower content of primary amine functional groups compared to Preparation Example 1, and consequently, lower carbonate mineralization efficiency.

[0114] Experimental Example 2. Evaluation of Carbonate Mineralization Efficiency According to Immersion Solution and Immersion Time

[0115] The polyamidoamine hydrogel of Preparation Example 1 above was immersed for 8 days in artificial seawater with a calcium ion concentration of 440 mg / L, an aqueous CaCl2 solution containing calcium ions of the same concentration, and actual seawater collected from Eulwangri and the West Sea, respectively, and the carbonate mineralization efficiency was evaluated by varying the immersion time as shown in Table 3 below.

[0117] division Hydrogel used Storage time (days) Immersion solution Carbonate mineralization efficiency (%) Example 1 Preparation Example 1 1 artificial seawater 15.55 Example 2' Preparation Example 1 2 artificial seawater 19.68 Example 3' Preparation Example 1 4 artificial seawater 24.38 Example 4' Preparation Example 1 6 artificial seawater 32.76 Example 5' Preparation Example 1 8 artificial seawater 36.9 Example 6' Preparation Example 1 8 calcium solution 19.35 Example 7' Preparation Example 1 8 actual seawater 25.99

[0119] As can be seen from Examples 1' to 5' in Table 2 above, it can be confirmed that the carbonate mineralization efficiency increases as the immersion time of the polyamidoamine hydrogel of Preparation Example 1 in artificial seawater increases. In addition, as can be confirmed from the scanning electron microscope image in Fig. 5 and the X-ray diffraction analysis in Fig. 6 below, it was found that the calcium carbonate prepared according to the method of the present invention has an aragonite-type crystal form. Meanwhile, as in Examples 6' and 7', even when the polyamidoamine hydrogel of Preparation Example 1 is immersed in a calcium aqueous solution and actual seawater in addition to artificial seawater, it can be confirmed that the polyamidoamine hydrogel has excellent carbonate mineralization efficiency.

[0121] Experimental Example 3. Evaluation of Carbonate Mineralization Efficiency According to Hydrogel Particle Size

[0122] The polyamidoamine hydrogel of Preparation Example 1 was ground using a grinder for 10 minutes, and the ground hydrogel was filtered through sieves with average grid diameters of 1,400 μm, 1,000 μm, 710 μm, and 410 μm, respectively, to produce polyamidoamine hydrogel particles having the following particle diameters. The prepared polyamidoamine hydrogel particles were immersed in artificial seawater for 4 days to evaluate carbonate mineralization efficiency.

[0124] division Hydrogel used Particle diameter (μm) Carbonate mineralization efficiency (%) Example 1a Preparation Example 1 1,400 35.02 Example 2a Preparation Example 1 1,000 31.40 Example 3a Preparation Example 1 710 30.02 Example 4a Preparation Example 1 410 29.43

[0126] As shown in Table 4 above, when the polyamidoamine hydrogel of Preparation Example 1 is ground into smaller particles, it can be confirmed that the specific surface area of ​​the polyamidoamine hydrogel increases, thereby increasing the carbonate mineralization efficiency. In particular, in the case of Examples 1a and 2a, where the diameter of the polyamidoamine hydrogel is 1,000 μm or more and 5,000 μm or less, the specific surface area is low, resulting in excellent reaction efficiency. At the same time, the hydrolysis rate of the hydrogel is slow, so the crystal nucleation performance of the calcium carbonate in the hydrogel is maintained for a longer period, and it was confirmed that the carbonate mineralization efficiency is very excellent.

[0128] Experimental Example 4. Evaluation of the biodegradability of polyamidoamine hydrogel

[0129] The polyamidoamine hydrogel of Preparation Example 1 above was immersed in distilled water to evaluate its biodegradability. After 2 months had passed since immersion, it was confirmed that the polyamidoamine hydrogel had been completely hydrolyzed. From the above experimental results, it was confirmed that polyamidoamine is easily biodegradable in distilled water as well as seawater.

Claims

Claim 1 A polyamidoamine hydrogel formed from an amine monomer and an acrylamide monomer, wherein the primary amine group content is 0.25 mmol / g or more. Claim 2 A polyamidoamine hydrogel according to claim 1, wherein the amine-based monomer comprises two or more amine groups within the monomer. Claim 3 A polyamidoamine hydrogel according to claim 1, wherein the acrylamide-based monomer comprises two or more acrylic groups within the monomer. Claim 4 A polyamidoamine hydrogel according to claim 1, wherein the amine-based monomer is one or more selected from the group consisting of ethylenediamine, 1,2-diaminopropane, 1,4-diaminobutane, hexamethylenediamine, diethylenetriamine, triethylenetetraamine, tris(2-aminoethyl)amine, diaminocyclohexane, and pentaethylenehexaamine. Claim 5 A polyamidoamine hydrogel according to claim 1, wherein the acrylamide-based monomer is one or more selected from the group consisting of N,N'-methylenebisacrylamide, N,N'-(1,2-dihydroxyethylene)bisacrylamide, and N,N'-ethylenebisacrylamide. Claim 6 In claim 1, the polyamidoamine hydrogel is a polyamidoamine hydrogel having a particle diameter of 1,000 μm or more and 5,000 μm or less. Claim 7 A method for producing calcium carbonate, wherein a polyamidoamine hydrogel according to any one of claims 1 to 6 is introduced into an aqueous calcium ion solution to produce calcium carbonate. Claim 8 A method for producing calcium carbonate according to claim 7, wherein the calcium carbonate has an aragonite-type crystal form. Claim 9 A method for producing calcium carbonate according to claim 7, wherein 1 kg or more of the polyamidoamine hydrogel is added per 1 L of the calcium ion aqueous solution. Claim 10 A method for preparing a polyamidoamine hydrogel comprising: a step (S10) of preparing a precursor mixture comprising an amine-based monomer, an acrylamide-based monomer, and an aqueous solvent; and a step (S20) of reacting the monomers in the precursor mixture to prepare a polyamidoamine, wherein the step (S20) is performed without stirring the precursor mixture, and the monomer content of the precursor mixture is 20 weight% or more. Claim 11 A method for preparing a polyamidoamine hydrogel according to claim 10, wherein the molar ratio of the amine-based monomer and the acrylamide-based monomer is 1:0.5 or more and 1:3 or less. Claim 12 A method for preparing a polyamidoamine hydrogel according to claim 10, wherein the above step (S10) involves a Michael addition reaction of the amine-based monomer and the acrylamide-based monomer. Claim 13 A method for preparing a polyamidoamine hydrogel according to claim 10, wherein the monomer content of the precursor mixture is 40% by weight or more and 80% by weight or less. Claim 14 A method for preparing a polyamidoamine hydrogel according to claim 10, wherein the above step (S20) is performed at a temperature of 50°C or higher and 100°C or lower.